Cyclic Microwave-Modified Sol-Gel Process of NaY(WO4)2:Ho3+/Yb3+ Phosphors and Their Upconversion Photoluminescence Properties - Sung Lim, Chang (Asian Journal of Chemistry, 2014)
NaY1-x(WO4)2:Ho3+/Yb3+ phosphors with doping concentrations of Ho3+ and Yb3+ (x = Ho3+ + Yb3+, Ho3+ = 0.05, 0.1, 0.2 and Yb3+ = 0.2, 0.45) were successfully synthesized by the cyclic microwave-modified sol-gel process and their upconversion properties were investigated. Well-crystallized particles showed a fine and homogeneous morphology with particle sizes of 2-5 μm. Under excitation at 980 nm, the synthesized particles exhibited yellow emissions based on a strong 550 nm emission band and a strong 655 nm emission band in the red region. The Raman spectra of the doped particles indicated the domination of strong peaks at higher frequencies and weak peaks at lower frequencies induced by the disorder of the [WO4]2- groups with the incorporation of the Ho3+ and Yb3+ lements into the crystal lattice or by a new phase formation.